Sedge weeds control in tropical turf using sea water - Uddin, Md Kamal; Juraimi, Abdul Shukor; Othman, Radziah; Shamsuzzaman, S. M.; Anwar, Md Parvez (Bangladesh Botanical Society, 2017)
Research was designed to reduce herbicide use by replacing post emergence herbicides with readily available sea water to control tropical weeds. Results showed that 5 species viz., Cyperus compressus L., Cyperus iria L., Fimbristylis miliaceae Vahl., Fimbristylis ovata J. Kern. and Scirpus juncoides Roxb. were very susceptible and effectively controlled (100%) with 72 dS/m salinity treatment, but. 2 species viz. Cyperus aromaticus Ridley. and Cyperus rotundus L. were extremely tolerant to the salinity level of 72 dS/m.